2021
DOI: 10.1136/ebmental-2021-300287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on telepsychiatry at the service and individual patient level across two UK NHS mental health Trusts

Abstract: BackgroundThe effects of COVID-19 on the shift to remote consultations remain to be properly investigated.ObjectiveTo quantify the extent, nature and clinical impact of the use of telepsychiatry during the COVID-19 pandemic and compare it with the data in the same period of the 2 years before the outbreak.MethodsWe used deidentified electronic health records routinely collected from two UK mental health Foundation Trusts (Oxford Health (OHFT) and Southern Health (SHFT)) between January and September in 2018, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…Finally, the study took place just before the outbreak of the COVID-19 pandemic in Israel and the questionnaires were completed before or at the very beginning of the COVID-19 era. The pandemic resulted in rapid assimilation of telemedicine and telepsychiatry in the world including in Israel ( 39 41 ), with higher odds of attending and completing treatment than FTF during this period ( 42 , 43 ). Mental health providers reported satisfaction with electronic health services ( 44 ), patients received telepsychiatry well as a solution for emergency situations when FTF meetings were not possible ( 45 ), and in a US study most patients said they would consider it in the future ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study took place just before the outbreak of the COVID-19 pandemic in Israel and the questionnaires were completed before or at the very beginning of the COVID-19 era. The pandemic resulted in rapid assimilation of telemedicine and telepsychiatry in the world including in Israel ( 39 41 ), with higher odds of attending and completing treatment than FTF during this period ( 42 , 43 ). Mental health providers reported satisfaction with electronic health services ( 44 ), patients received telepsychiatry well as a solution for emergency situations when FTF meetings were not possible ( 45 ), and in a US study most patients said they would consider it in the future ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter are unlikely to explain all the reduction. For example, a recent study on mental health and telepsychiatry showed that the rapid shift to remote service delivery has not reached some groups of patients (in particular patients with dementia and mild cognitive impairment) who may require more tailored management 24 . Dementia was not widely represented in our results, perhaps being covered by a range of CTv3 codes; we will conduct further research on the impacts of COVID on dementia in primary care to capture this fully.…”
Section: Mental Healthmentioning
confidence: 99%
“…At the start of the COVID-19 pandemic, mental health services around the world, along with health services in general, needed to adapt quickly to reduce the risk of infection and transmission while continuing to support those with mental health problems [ 1 ]. However, as identified early in the COVID-19 pandemic by the World Health Organization (WHO), the pandemic went beyond the physical threat to also affect mental health [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prompted by this, several countries modified national telemedicine regulations to promote its spread [ 16 ]. However, it is unclear whether the apparently rapid transition to TMH observed in many high-income countries [ 1 ] has occurred globally, which services have been affected, and whether this change has been sustained through the different phases of the pandemic.…”
Section: Introductionmentioning
confidence: 99%